Can Union Labor ever Cost Less? - Allen, Steven G. (Quarterly Journal of Economics, 1987)
This paper examines the effect of unions on efficiency by estimating cost function systems over three different sets of construction projects. The results show that union contractors have greater economies of scale. This gives them a cost advantage in large commercial office buildings, but in school and hospital construction, nonunion contractors have lower costs at all output levels. Despite the cost differences, profits for nonunion contractors in school and hospital construction are no higher than those for union contractors because the burden of higher union costs is shifted to buyers.